Cannabis use and lung cancer: time to stop overlooking the problem?. Issue 5 (20th May 2021) - Betser, Léa; Glorion, Matthieu; Mordant, Pierre; Caramella, Caroline; Ghigna, Maria-Rosa; Besse, Benjamin; Planchard, David; Le Pavec, Jérome; Chapelier, Alain; Friard, Sylvie; Gounant, Valérie; Castier, Yves; et al.
After tobacco, cannabis is the most widely used drug worldwide, and the move to legalise it is growing in more and more countries. The literature about the involvement of cannabis smoking on the development of lung cancer is scarce and most often reassuring [1–3], even though the concentration of carcinogens in cannabis smoke is unquestionably greater than that in tobacco smoke [4]. Moreover, recent studies on cannabis tend to focus on possible therapeutic effects [5]. Studies of the carcinogenic impact of cannabis are indeed limited by its frequent association with tobacco smoking and by its illegal status in most countries [6]. Cannabis smoking is highly prevalent and largely underreported in young patients with resected nonsmall cell lung cancer. This is a major issue as co-consumption of cannabis and tobacco may lead to more severe and advanced forms of lung cancer. https://bit.ly/39tvsAm